PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERPIKIR LOGIS SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV DI MI NURUL QUR’AN PAGUTAN TAHUN PELAJARAN 2024/2025 - Luluk irani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the low logical abilities of fourth-grade students in Mathematics at MI Nurul Qur’an Pagutan. This study aims to determine the effect of the Problem-Based Learning model on students’ logical and critical thinking skills. The research used a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The sample consisted of class IVA (21 students) as the experimental group and class IVC (20 students) as the control group. Data collection techniques included tests, observation, and documentation. The data analysis involved normality and homogeneity tests, followed by hypothesis testing using the t-test with polled variance. The results indicated a significance value of 0.001 < 0.05, meaning H₀ is rejected and Hₐ is accepted. Thus, the Problem-Based Learning model has a significant effect on students’ logical and critical thinking abilities.